Aqueous magnesium ion positive electrode material nickel oxyhydroxide / carbon nanotube composite and its preparation method and application
By growing nickel hydroxyoxide particles on the surface of carbon nanotubes, a nickel hydroxyoxide/carbon nanotube composite was prepared, which solved the problem of limited selection of positive electrode materials for aqueous magnesium ion batteries, and achieved a magnesium ion storage effect with high capacity and excellent cycle stability.
Patent Information
- Application Number
- CN202310066012.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-17
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-01-17
AI Technical Summary
The selection of positive electrode materials for existing water-based magnesium ion batteries is limited, and the diffusion kinetic properties of magnesium ion are poor, which restricts the transport capacity of magnesium ions and affects the rate performance and theoretical capacity of the battery.
The chemical bath method was used to grow nickel hydroxyoxide particles on the surface of carbon nanotubes, and a nickel hydroxyoxide/carbon nanotube composite was prepared as the positive electrode material for aqueous magnesium ion batteries.
The complex exhibits excellent electrochemical cycling stability and magnesium ion storage capability, with high capacity (about 135 mAh·g-1) and a flat charge and discharge platform (about 0.58V) in 1M magnesium chloride electrolyte solution.
Smart Images

Figure CN116062808B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of inorganic nanomaterials, and in particular to an aqueous magnesium ion positive electrode material nickel oxyhydroxide / carbon nanotube composite and a preparation method and application thereof. Background Art
[0002] In recent years, energy storage has attracted extensive attention from researchers around the world as an intermediate step to achieve comprehensive, clean and efficient utilization of energy. In particular, with the large-scale grid connection of random and volatile renewable energy and the large-scale access of interactive devices such as electric vehicles and distributed power sources, the power system will present the characteristics of a high proportion of renewable energy and a high proportion of power electronics. In order to achieve the load balance of the new power system with new energy as the main body, energy storage technology will play an important role. Traditional energy storage systems, such as supercapacitors, lithium-ion batteries and flow batteries, however, these traditional energy storage systems have safety hazards and high costs. Therefore, aqueous batteries came into being. Compared with many aqueous batteries, magnesium has abundant resources, low prices, non-toxic or low-toxic compounds, and safety. Therefore, aqueous magnesium ion batteries have the advantages of green environmental protection, low cost, and high safety. In addition, they use multiple electron transfer paths during the charging and discharging process to achieve high energy and high power density, and are expected to become one of the next generation of important energy storage devices. However, due to the small size, high charge density and strong polarization of magnesium ions, it is difficult to form embedded compounds. Therefore, the choice of positive electrode materials for magnesium ion batteries is limited, and the magnesium ion diffusion kinetics of most electrode materials are poor, which restricts the transport capacity of magnesium ions in the electrode materials, affects the rate performance of the battery, and makes it difficult to achieve the theoretical capacity and ideal rate performance. Therefore, the research and development of positive electrode materials is crucial to the development and application of aqueous magnesium ion batteries.
[0003] At present, the main research direction of positive electrode materials is to find materials that allow reversible insertion / deintercalation of magnesium ions during the charging and discharging process and can exist stably in the electrolyte.
[0004] Alkaline electrolytes are usually corrosive and will corrode metal-based anodes, resulting in poor electrochemical stability. In addition, if the electrolyte leaks, it is easy to cause safety problems, which seriously hinders its large-scale application. Compared with alkaline batteries, neutral batteries have become the best choice in aqueous batteries due to their excellent safety and low corrosiveness of neutral electrolytes. On the other hand, among the many positive electrode materials, transition metal oxides such as manganese-based and vanadium-based are the main research objects because of their advantages of low cost and high capacity. Nickel-based compounds are rarely used as positive electrode materials for batteries due to their high conversion potential between divalent nickel ions and trivalent nickel ions and low window of electrochemical stability in aqueous electrolytes, especially aqueous magnesium ion positive electrode materials. Generally, nickel-based compounds are used as negative electrode materials for lithium batteries. As a common positive electrode material for nickel-based batteries, nickel-based compounds have the advantages of easy availability of raw materials, low price, and environmental friendliness. It is one of the most widely studied positive electrode materials for nickel-based batteries. However, the negative electrode material will be continuously deposited on the surface of the nickel hydroxide positive electrode during the charge and discharge process, blocking the liquid phase mass transfer channel, causing the positive electrode to be poisoned and the battery to fail, making it have the disadvantages of low specific capacity, poor cycle stability and low utilization rate as a positive electrode material for nickel-based batteries. In particular, when it is used as a positive electrode material for aqueous magnesium ion batteries, due to the disadvantages of magnesium ions such as small size, high charge density and formation of embedded compounds, nickel-based compounds cannot be used as positive electrode materials in aqueous magnesium ion batteries.
[0005] Wang Xiaofeng et al., in "Electrochemical Behavior of Nickel Oxide Deposited on Carbon Nanotube Surface and Its Supercapacitor", Journal of Inorganic Chemistry Vol. 18, No. 2, 2003.3, disclosed a composite electrode obtained by electrochemically depositing nickel oxide on the surface of carbon nanotubes. The supercapacitor based on the composite electrode has good reversibility and improves the performance of nickel oxide. Chinese invention patent CN103131211A discloses a carbon nanotube-lithium-titanium doped nickel oxide compound and its preparation method, which adopts the method of grafting lithium-titanium doped nickel oxide on the surface of carbon nanotubes to obtain a compound to prepare a material with both high dielectric constant and low dielectric loss. However, the above-mentioned disclosed technologies all have the problems of complex processing technology and high production cost. Summary of the invention
[0006] The invention discloses a nickel oxyhydroxide / carbon nanotube composite of an aqueous magnesium ion positive electrode material and a preparation method and application thereof. The composite is a high-valent nickel-based compound used as a positive electrode material for an aqueous magnesium ion battery and carbon nanotubes. The preparation method is mild, simple to operate, safe and environmentally friendly, has a stable structure, and has excellent electrochemical properties.
[0007] To achieve the above-mentioned purpose, the present invention provides the following technical scheme, a nickel oxyhydroxide / carbon nanotube composite of an aqueous magnesium ion positive electrode material and a preparation method and application thereof, wherein the nickel oxyhydroxide / carbon nanotube composite is prepared by growing nickel oxyhydroxide particles on the surface of the carbon nanotube using a chemical bath method using carbon nanotubes as a substrate. The nickel oxyhydroxide is uniformly distributed on the surface of the carbon nanotube using this method to form a nickel oxyhydroxide / carbon nanotube composite.
[0008] Preferably, the process steps of the chemical bath method include:
[0009] S1. Mix nickel sulfate hexahydrate, potassium persulfate and deionized water and stir at a uniform speed to form a uniform seed layer solution;
[0010] S2. Add ammonia water dropwise to the seed layer solution and stir at a uniform speed until the reaction is complete to obtain a precursor solution;
[0011] S3. Add carbon nanotubes to the precursor solution, stir at a constant speed, react for 20 to 30 minutes, and then dry to obtain a nickel oxyhydroxide / carbon nanotube composite. The carbon nanotubes are pretreated before use, including washing the carbon nanotubes with water and / or ethanol solution, and drying in a 50 to 70° C. air drying oven for 30 to 60 minutes.
[0012] In the above step, the divalent nickel is oxidized to high-valent trivalent nickel by the strong oxidant potassium persulfate, which is converted to nickel oxyhydroxide under alkaline conditions and then deposited on the surface of the carbon nanotubes through hydrogen bonding to form a nickel oxyhydroxide / carbon nanotube composite.
[0013] Preferably, in S1, the mass ratio of nickel sulfate hexahydrate to potassium persulfate in the seed layer solution is (7-8): (3-4).
[0014] Preferably, in S2, the concentration of the ammonia water added to the precursor solution is 28 wt %, and the volume ratio of the ammonia water to the seed layer solution is 1:10-30.
[0015] Preferably, in S3, after the reaction is completed, the drying process includes placing the carbon nanotubes in a forced air drying oven at 50-70° C. for 30-90 minutes to obtain the nickel oxyhydroxide / carbon nanotube composite.
[0016] Preferably, in S1-S3, the reaction conditions are: temperature of 25-35° C.; and uniform stirring speed of 500-1000 rpm.
[0017] Generally, nickel oxyhydroxide in nickel-based compounds can be widely used as alkaline electrolyte electrode materials in energy storage and conversion. Nickel oxyhydroxide is a common layered inorganic compound in nickel-based compounds, which has the advantages of simple preparation process, low toxicity and high redox activity. Nickel oxyhydroxide is derived from nickel hydroxide by oxidative dehydrogenation. The oxygen vacancies and more defects in it are conducive to providing reactive sites, increasing the adsorption capacity of hydrated magnesium ions, and providing sufficient reactivity for the embedding of magnesium ions. In addition, the defects and vacancies in nickel oxyhydroxide are also conducive to compounding with carbon substrates with poor hydrophilicity, thereby increasing the conductivity of the composite material and further improving the reaction kinetics rate.
[0018] The present invention adopts the nickel oxyhydroxide / carbon nanotube composite prepared by the above technical scheme, takes carbon nanotubes as a substrate, uses a high-valent nickel-based compound as a seed layer, and uses a chemical bath method to grow nickel oxyhydroxide particles on the surface of the carbon nanotubes to prepare the nickel oxyhydroxide / carbon nanotube composite, and the nickel oxyhydroxide is evenly distributed on the surface of the carbon nanotubes. In the present invention, a strong oxidant is used to convert low-valent nickel into a stable high-valent nickel-based compound, and the prepared nickel oxyhydroxide / carbon nanotube composite is used as a working electrode, and a platinum wire and silver / silver chloride are used as a counter electrode and a reference electrode respectively, and are applied to an aqueous magnesium ion battery using a 1M magnesium chloride aqueous solution as an electrolyte. Through electrochemical signal testing, it can have excellent cycle stability and excellent magnesium ion storage capacity.
[0019] The technical effects of the technical solution of the present invention are as follows:
[0020] 1. By adopting the technical solution of the present invention, nickel oxyhydroxide nanoparticles are synthesized on the surface of carbon nanotubes by a simple chemical bath method, and the nickel oxyhydroxide nanoparticles are deposited on the surface of carbon nanotubes to form a nickel oxyhydroxide / carbon nanotube composite, which is used as a positive electrode material for an aqueous magnesium ion battery, and has excellent electrochemical cycle stability and magnesium ion storage capacity. In a 1M magnesium chloride electrolyte solution, the nickel oxyhydroxide / carbon nanotube composite exhibits a high capacity (about 135 mAh·g -1 ) and a flat charge-discharge platform (about 0.58 V, vs. Ag / AgCl).
[0021] 2. The high-valent nickel-based compound of the aqueous magnesium ion positive electrode material provided by the technical solution of the present invention has the advantages of safety, environmental protection, stable structure, mild preparation method and simple operation.
[0022] 3. Through the technical solution of the present invention, nickel-based compounds are applied to aqueous magnesium-ion batteries, which expands the range of available positive electrode materials for aqueous magnesium-ion batteries and has the advantages of easy availability of raw materials, low price and environmental friendliness. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 XRD schematic diagram of the nickel oxyhydroxide / carbon nanotube composite prepared in Example 1 of the present invention.
[0024] Figure 2a A low-magnification SEM photograph of the nickel oxyhydroxide / carbon nanotube composite prepared in Example 1 of the present invention.
[0025] Figure 2b A high-magnification SEM photograph of the nickel oxyhydroxide / carbon nanotube composite prepared in Example 1 of the present invention.
[0026] Figure 3a Linear cyclic voltammograms of the carbon nanotubes and the nickel oxyhydroxide / carbon nanotube composite prepared in Example 1 of the present invention.
[0027] Figure 3b The charge and discharge performance diagram of the carbon nanotubes and the nickel oxyhydroxide / carbon nanotube composite prepared in Example 1 of the present invention.
[0028] Figure 4a The charge-discharge performance graph and rate performance graph of the carbon nanotubes and nickel oxyhydroxide / carbon nanotube composite prepared in Example 1 of the present invention in different electrolytes.
[0029] Figure 4b Rate performance diagram of the carbon nanotubes and nickel oxyhydroxide / carbon nanotube composite prepared in Example 1 of the present invention in different electrolytes.
[0030] Figure 5a Rate performance diagram of the carbon nanotubes and nickel oxyhydroxide / carbon nanotube composite prepared in Example 1 of the present invention in 1M magnesium chloride solution.
[0031] Figure 5b Cyclic stability diagram of the carbon nanotubes and nickel oxyhydroxide / carbon nanotube composite prepared in Example 1 of the present invention in 1M magnesium chloride solution. DETAILED DESCRIPTION
[0032] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the protection scope of the present invention.
[0033] The present invention provides a nickel oxyhydroxide / carbon nanotube composite of an aqueous magnesium ion positive electrode material and a preparation method and application thereof. Carbon nanotubes are used as substrates, and nickel oxyhydroxide particles are grown on the surface of the carbon nanotubes by a chemical bath method to prepare the nickel oxyhydroxide / carbon nanotube composite.
[0034] The chemical bath method includes mixing nickel sulfate hexahydrate, potassium persulfate and water, stirring at a uniform speed to form a uniform seed layer solution; then adding ammonia water dropwise to the seed layer solution, stirring at a uniform speed until the reaction is complete, and then a precursor solution can be obtained; finally, carbon nanotubes are added to the precursor solution, stirring at a uniform speed, and nickel oxyhydroxide particles are uniformly precipitated on the surface of the carbon nanotubes. After reacting for 20 to 30 minutes and drying, a nickel oxyhydroxide / carbon nanotube composite can be obtained.
[0035] The technical solution of the present invention is further described in detail below through specific embodiments.
[0036] Example 1
[0037] This embodiment provides an aqueous magnesium ion positive electrode material nickel oxyhydroxide / carbon nanotube composite and a preparation method and application thereof, including the following specific steps:
[0038] (1) Preparation of nickel oxyhydroxide / carbon nanotube composite electrode: Using carbon nanotubes as a substrate, nanostructured nickel oxyhydroxide particles are grown on their surface using a simple and mild chemical bath method.
[0039] Specifically, take an appropriate amount of deionized water and anhydrous ethanol solution to treat the surface of carbon nanotubes, and then place them in a forced air drying oven at a temperature of 50°C for 40 minutes. Take an appropriate volume of deionized water, add 100 mg / mL of nickel sulfate hexahydrate and 40 mg / mL of potassium persulfate, respectively, in a volume ratio of 1:2, and stir at a constant speed for 10 minutes to form a seed layer solution. Add 28 wt% ammonia water dropwise to the above seed layer solution, the volume ratio of ammonia water to the seed layer solution is 1:10, and stir at room temperature for 2 minutes to form a precursor solution. Take an appropriate amount of carbon nanotubes and place them in the above precursor solution, stir at a constant speed for 20 minutes at room temperature, filter the sample after the reaction is completed, and place it in a forced air drying oven at 50°C for 30 minutes to obtain a nickel hydroxide / carbon nanotube composite.
[0040] See also Figure 1 , is a schematic diagram of the XRD of the nickel oxyhydroxide / carbon nanotube composite prepared in step (1) of this embodiment. Compared with the XRD characteristic peaks of carbon nanotubes, the main characteristic peaks of the nickel oxyhydroxide / carbon nanotube composite are located at 13.4°, 33.9° and 42.2°, respectively, indicating that the nickel oxyhydroxide / carbon nanotube composite is successfully prepared.
[0041] See also Figure 2a and Figure 2b , is a low-magnification SEM photograph of the nickel oxyhydroxide / carbon nanotube composite prepared in step (1) of this example ( Figure 2a ) and high magnification SEM photos ( Figure 2b), nickel oxyhydroxide nanoparticles are distributed on the surface of carbon nanotubes.
[0042] (2) Test of nickel oxyhydroxide / carbon nanotube composite electrode: The prepared nickel oxyhydroxide / carbon nanotube composite was used as the working electrode, platinum wire and silver / silver chloride were used as the counter electrode and reference electrode respectively, and 1M magnesium chloride aqueous solution was used as the electrolyte to carry out the electrochemical signal test of the three-electrode system. In 1M magnesium chloride aqueous solution, the capacity of the nickel oxyhydroxide / carbon nanotube composite was about 135 mAh·g -1 , the discharge platform is about 0.58V.
[0043] See also Figure 3a and Figure 3b , respectively, are the linear cyclic voltammogram and charge-discharge performance diagram of the nickel oxyhydroxide / carbon nanotube composite prepared in step (1) of this embodiment. The linear cyclic voltammogram of the nickel oxyhydroxide / carbon nanotube composite shows an obvious redox peak, confirming that it can undergo electrochemical behavior of magnesium ion embedding / de-embedding, and the charge-discharge performance diagram further illustrates that it has a relatively high capacity and discharge platform.
[0044] See also Figure 4a and 4b , respectively, are the charge-discharge performance graph and rate performance graph of the nickel oxyhydroxide / carbon nanotube composite prepared in step (1) of this embodiment in different electrolytes. As can be seen from the comparison of the figures, compared with 1M potassium hydroxide electrolyte, the nickel oxyhydroxide / carbon nanotube composite exhibits a higher discharge platform and excellent cycle stability in 1M magnesium chloride electrolyte.
[0045] See also Figure 5a and Figure 5b , respectively, are the rate performance graph and cycle stability graph of the nickel oxyhydroxide / carbon nanotube composite prepared in step (1) of this example in 1M magnesium chloride solution. After 200 cycles, the capacity of the nickel oxyhydroxide / carbon nanotube composite remains about 97% of the initial capacity.
[0046] Example 2
[0047] This embodiment provides a method for preparing a nickel oxyhydroxide / carbon nanotube composite electrode, comprising the following specific steps:
[0048] (1) Preparation of nickel oxyhydroxide / carbon nanotube composite electrode: Using carbon nanotubes as a substrate, nanostructured nickel oxyhydroxide particles are grown on their surface using a simple and mild chemical bath method.
[0049] Specifically, take an appropriate amount of deionized water and anhydrous ethanol solution to treat the surface of carbon nanotubes, and then place them in a blast drying oven at a temperature of 50°C for 40 minutes. Take an appropriate volume of deionized water, add 100 mg / mL of nickel sulfate hexahydrate and 40 mg / mL of potassium persulfate, respectively, in a volume ratio of 1:1.5, and stir at a constant speed for 10 minutes to form a seed layer solution. Add 28wt% ammonia water dropwise to the above seed layer solution, the volume ratio of ammonia water to the seed layer solution is 1:10, stir at room temperature for 2 minutes to form a precursor solution. Take an appropriate amount of carbon nanotubes and place them in the above precursor solution, stir at a constant speed for 30 minutes at room temperature, filter the sample after the reaction is completed, and place it in a blast drying oven at 50°C for 30 minutes to obtain a nickel hydroxide / carbon nanotube composite.
[0050] (2) Test of nickel oxyhydroxide / carbon nanotube composite electrode: The prepared nickel oxyhydroxide / carbon nanotube composite was used as the working electrode, platinum wire and silver / silver chloride were used as the counter electrode and reference electrode respectively, and 1M magnesium chloride aqueous solution was used as the electrolyte to carry out the electrochemical signal test of the three-electrode system. In 1M magnesium chloride aqueous solution, the capacity of the nickel oxyhydroxide / carbon nanotube composite was about 132 mAh·g -1 , the discharge platform is about 0.58 V. After 200 cycles, the capacity of the nickel oxyhydroxide / carbon nanotube composite remains about 95% of the initial capacity.
[0051] Example 3
[0052] This embodiment provides a method for preparing a nickel oxyhydroxide / carbon nanotube composite electrode, comprising the following specific steps:
[0053] (1) Preparation of nickel oxyhydroxide / carbon nanotube electrode: Using carbon nanotubes as a substrate, nanostructured nickel oxyhydroxide particles are grown on the surface of the carbon nanotubes using a simple and mild chemical bath method.
[0054] Specifically, take an appropriate amount of deionized water and anhydrous ethanol solution to treat the surface of carbon nanotubes, and then place them in a forced air drying oven at a temperature of 50°C for 40 minutes. Take an appropriate volume of deionized water, add 100 mg / mL of nickel sulfate hexahydrate and 40 mg / mL of potassium persulfate, respectively, in a volume ratio of 1:2, and stir at a constant speed for 10 minutes to form a seed layer solution. Add 28wt% ammonia water dropwise to the above seed layer solution, the volume ratio of ammonia water to the seed layer solution is 1:10, and stir at room temperature for 2 minutes to form a precursor solution. Take an appropriate amount of carbon nanotubes and place them in the above precursor solution, stir at a constant speed for 40 minutes at room temperature, and after the reaction is completed, filter the sample and place it in a forced air drying oven at 50°C for 30 minutes to obtain a nickel hydroxide / carbon nanotube composite.
[0055] (2) Test of nickel oxyhydroxide / carbon nanotube composite electrode: The prepared nickel oxyhydroxide / carbon nanotube composite was used as the working electrode, platinum wire and silver / silver chloride were used as the counter electrode and reference electrode respectively, and 1M magnesium chloride aqueous solution was used as the electrolyte to carry out the electrochemical signal test of the three-electrode system. In 1M magnesium chloride aqueous solution, the capacity of the nickel oxyhydroxide / carbon nanotube composite was about 134 mAh·g -1 , the discharge platform is about 0.58 V. After 200 cycles, the capacity of the nickel oxyhydroxide / carbon nanotube composite remains about 96% of the initial capacity.
[0056] Comparison Example
[0057] This comparative example provides a method for preparing a nickel hydroxide electrode, comprising the following specific steps:
[0058] (1) Preparation of nickel hydroxide electrode: Nanostructured nickel hydroxide is grown and prepared by a simple and mild chemical bath method.
[0059] Take an appropriate amount of deionized water, add nickel sulfate hexahydrate with a volume concentration of 100 mg / mL, and stir at a constant speed for 10 minutes to form a seed layer solution. Add 28wt% ammonia water dropwise to the above seed layer solution, the volume ratio of ammonia water to seed layer solution is 1:10, and stir at room temperature for 4 hours. After the reaction is completed, filter the sample and place it in a blast drying oven at 50°C for 30 minutes to obtain nanostructured nickel hydroxide.
[0060] (2) Test of nickel hydroxide electrode: The prepared nickel hydroxide was used as the working electrode, platinum wire and silver / silver chloride were used as the counter electrode and reference electrode respectively, and 1M magnesium chloride aqueous solution was used as the electrolyte to carry out the electrochemical signal test of the three-electrode system. In 1M magnesium chloride aqueous solution, nickel hydroxide has no chemical signal peak, indicating that nickel hydroxide has no electrochemical magnesium storage performance.
[0061] It can be seen from the above examples that the nickel oxyhydroxide / carbon nanotube composite prepared by the present invention is used as a working electrode in an aqueous magnesium ion battery, which has excellent electrochemical cycle stability and magnesium ion storage capacity. In a 1M magnesium chloride electrolyte solution, the nickel oxyhydroxide / carbon nanotube composite exhibits a high capacity (132-135 mAh·g -1 ) and a flat charge-discharge platform (about 0.58 V, vs. Ag / AgCl).
[0062] By comparing Examples 1-3 with the control example, it can be seen that the nickel oxyhydroxide / carbon nanotube composite prepared by the technical solution of the present invention overcomes the technical problem in the prior art that nickel hydroxide cannot be used as a working electrode in an aqueous magnesium ion battery. The results of Examples 1-3 show that the nickel oxyhydroxide / carbon nanotube composite prepared by the technical solution of the present invention has excellent electrochemical cycle stability and magnesium ion storage capacity when applied to an aqueous magnesium battery.
[0063] The above are only preferred embodiments of the present invention, which do not limit the protection scope of the present invention. For those skilled in the art, the present invention may have various modifications and changes. Within the spirit and principle of the present invention, changes, modifications, replacements, integrations and parameter changes to these embodiments by conventional substitutions or by being able to achieve the same functions without departing from the principles and spirit of the present invention all fall within the protection scope of the present invention.
Claims
1. A use of a nickel oxyhydroxide / carbon nanotube composite as an aqueous magnesium ion positive electrode material, characterized in that: The preparation method of the nickel oxyhydroxide / carbon nanotube composite is as follows: using carbon nanotubes as a substrate, growing nickel oxyhydroxide particles on the surface of the carbon nanotubes by a chemical bath method, so that the nickel oxyhydroxide is evenly distributed on the surface of the carbon nanotubes, and preparing the nickel oxyhydroxide / carbon nanotube composite; the process of the chemical bath method includes: S1. Mix nickel sulfate hexahydrate, potassium persulfate and deionized water and stir at a uniform speed to form a uniform seed layer solution; S2. Add ammonia water dropwise to the seed layer solution, stir at a constant speed, and after the reaction is complete, a precursor solution can be obtained; S3. Add carbon nanotubes to the precursor solution, stir at a constant speed, react for 20 to 30 minutes and then dry to obtain the nickel oxyhydroxide / carbon nanotube composite; In S1, the mass ratio of nickel sulfate hexahydrate to potassium persulfate in the seed layer solution is (7-8): (3-4); In S1-S3, the reaction conditions are a temperature of 25-35°C.
2. The use according to claim 1, characterized in that In S2, the concentration of ammonia water added to the precursor solution is 28 wt %, and the volume ratio of ammonia water to the seed layer solution is 1:10-30.
3. The use according to claim 1, characterized in that In S3, after the reaction is completed, the drying process includes placing the carbon nanotubes in a forced air drying oven at 50-70° C. for 30-90 min to obtain the nickel oxyhydroxide / carbon nanotube composite.
4. The use according to any one of claims 1 to 3, characterized in that: In S1-S3, the speed of uniform stirring is 500~1000 rpm.
5. An aqueous magnesium ion battery, comprising an aqueous magnesium ion positive electrode material; the aqueous magnesium ion positive electrode material comprises a nickel oxyhydroxide / carbon nanotube composite prepared by a method for preparing a nickel oxyhydroxide / carbon nanotube composite; The preparation method of the nickel oxyhydroxide / carbon nanotube composite is as follows: using carbon nanotubes as a substrate, growing nickel oxyhydroxide particles on the surface of the carbon nanotubes by a chemical bath method, so that the nickel oxyhydroxide is evenly distributed on the surface of the carbon nanotubes, and preparing the nickel oxyhydroxide / carbon nanotube composite; the process of the chemical bath method includes: S1. Mix nickel sulfate hexahydrate, potassium persulfate and deionized water and stir at a uniform speed to form a uniform seed layer solution; S2. Add ammonia water dropwise to the seed layer solution, stir at a constant speed, and after the reaction is complete, a precursor solution can be obtained; S3. Add carbon nanotubes to the precursor solution, stir at a constant speed, react for 20 to 30 minutes and then dry to obtain the nickel oxyhydroxide / carbon nanotube composite; In S1, the mass ratio of nickel sulfate hexahydrate to potassium persulfate in the seed layer solution is (7-8): (3-4); In S1-S3, the reaction conditions are a temperature of 25-35°C.
6. An electrochemical energy storage device, characterized in that: It includes an aqueous magnesium ion positive electrode material; the aqueous magnesium ion positive electrode material includes a nickel oxyhydroxide / carbon nanotube composite prepared by a method for preparing a nickel oxyhydroxide / carbon nanotube composite: The preparation method of the nickel oxyhydroxide / carbon nanotube composite is as follows: using carbon nanotubes as a substrate, growing nickel oxyhydroxide particles on the surface of the carbon nanotubes by a chemical bath method, so that the nickel oxyhydroxide is evenly distributed on the surface of the carbon nanotubes, and preparing the nickel oxyhydroxide / carbon nanotube composite; the process of the chemical bath method includes: S1. Mix nickel sulfate hexahydrate, potassium persulfate and deionized water and stir at a uniform speed to form a uniform seed layer solution; S2. Add ammonia water dropwise to the seed layer solution, stir at a constant speed, and after the reaction is complete, a precursor solution can be obtained; S3. Add carbon nanotubes to the precursor solution, stir at a constant speed, react for 20 to 30 minutes and then dry to obtain the nickel oxyhydroxide / carbon nanotube composite; In S1, the mass ratio of nickel sulfate hexahydrate to potassium persulfate in the seed layer solution is (7-8): (3-4); In S1-S3, the reaction conditions are a temperature of 25-35°C.
Citation Information
Patent Citations
Carbon nano tube-lithium titanium doped nickel oxide compound and preparation method thereof
CN103131211A
Electrochemical cell
TWI532242B